2006
DOI: 10.4049/jimmunol.177.4.2314
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Fate of Endocytosed CCR7 and Its Ligands: Recycling versus Degradation

Abstract: The chemokine receptor CCR7 and its ligands CCL19 and CCL21 play a crucial role for the homing of lymphocytes and dendritic cells to secondary lymphoid tissues. Nevertheless, how CCR7 senses the gradient of chemokines and how migration is terminated are poorly understood. In this study, we demonstrate that CCR7(-GFP) is endocytosed into early endosomes containing transferrin receptor upon CCL19 binding, but less upon CCL21 triggering. Internalization of CCR7 was independent of lipid rafts but relied on dynamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
169
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(189 citation statements)
references
References 63 publications
20
169
0
Order By: Relevance
“…Over time, the synergistic activities will be overcome by a persistent production of inflammatory chemokines that will lead to high concentrations of CCL2 and CCL7, rendering CCR2 activity independent from non-ligand chemokines. A recent report on the fate of CCR7 and its ligands CCL19 and CCL21 showed different destinies for the receptor and the agonist [38]. Internalization and re-expression experiments indicated that reexpressed CCR7 is fully active and can mediate chemotaxis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Over time, the synergistic activities will be overcome by a persistent production of inflammatory chemokines that will lead to high concentrations of CCL2 and CCL7, rendering CCR2 activity independent from non-ligand chemokines. A recent report on the fate of CCR7 and its ligands CCL19 and CCL21 showed different destinies for the receptor and the agonist [38]. Internalization and re-expression experiments indicated that reexpressed CCR7 is fully active and can mediate chemotaxis.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the chemokine receptor, different intracellular destinies have been proposed after agonist-induced internalization [36][37][38]. The data we have obtained on CCR2 internalization prompted us to investigate the re-expression rate of the receptor after CCL7-or CCL7 plus CCL21-induced stimulation (Fig.…”
Section: Re-expressed Ccr2 Is Fully Functional and Can Mediate Cellulmentioning
confidence: 99%
“…Both ligands have similar affinity to CCR7 (4,5), but drive different fates: CCL19 signaling leads to receptor internalization and temporal desensitization while CCL21 can signal from the cell membrane (6,9,40,44,45), a well described liganddependent process for G-protein-coupled receptors. This differential fate of activated CCR7 could lead to increased receptor density and signaling on the cell side dominated by CCL21 (46), consistent with our observation of increased DC response to CCL21 gradients above 50 nM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The chemokine receptor CCR7, for instance, follows the clathrin-dependent pathway involving dynamin, Eps15, Rab5 and early endosomal antigen-1 (EEA1) [19,20]. After internalization, CCR7 enters the recycling compartment and traffics back to the plasma membrane to actively participate in directed cell migration, whereas its ligand CCL19 is sorted to lysosomes for degradation [19].…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
“…After internalization, CCR7 enters the recycling compartment and traffics back to the plasma membrane to actively participate in directed cell migration, whereas its ligand CCL19 is sorted to lysosomes for degradation [19]. Interestingly, ubiquitylation of CCR7 serves as control mechanism for receptor trafficking as an ubiquitylationdeficient mutant on one hand reduces the intracellular pool of CCR7 in the steady-state and, on the other hand, shows a significant retardation in receptor recycling after ligandmediated endocytosis, resulting in a reduced CCR7 surface pool and in inefficient cell migration [21].…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%